An Analysis on the Ternary Quadratic Diophantine Equation r\(^2\) + t\(^2\) = 10w\(^2\) - G. Janaki; S. Shanmuga Priya (Explorations in Diophantine Equations, 2023)
In this work, our main focus is on tracing all the non-zero, infinitely many integral solutions to the ternary quadratic equation\(r^2\) + \(r^2\) = 10\(w^2\). Of these solutions, some dazzling patterns are shown.